The moss flora of Britain and Ireland - Smith, A. J. E. 1935- (Cambridge University Press, 2004)
This book describes and illustrates in detail the 760 species of mosses currently known to occur in the British Isles and incorporates the most up-to-date information available on classification and nomenclature, together with recent synonyms. The species descriptions provide information on frequency, ecology, geographical relationships and distribution, including information on protected species and those species at risk. For many species there are footnotes to aid identification. In addition to the species descriptions there are descriptions of families and genera and also introductory information on conservation, collection, preservation and examination of material, together with advice on using the keys. An artificial key to genera provides the only workable comprehensive key published in the English language. This second edition incorporates the very considerable advances in our knowledge of mosses made in the last quarter of the twentieth century and will provide a unique resource for all concerned with these fascinating organisms